Rhetorical structures, strategies, and linguistic features of problem statement to promote a teaching writing model - Rustipa, Katharina; Purwanto, Sugeng; Rozi, Fahrur (Universitas Syiah Kuala, 2023)
Studies about rhetorical moves in the introduction section have been widely conducted. However, the studies focusing on the research problem statement is still limited. This current study investigated the rhetorical structures, strategies, and linguistic features of the problem statement written by undergraduate students, which aimed to contribute to the teaching model in teaching academic writing. This research was a qualitative case study belonging to genre analysis, using Swales CARS model. Thirty undergraduate students problem statement texts were explored, and interviewers were further conducted to collect the data. The results indicated that nine types of rhetorical structures were employed, most of which were characterized as incomplete. The rhetorical strategies employed by the students were making a centrality claim, making topic generalizations, reviewing previous research, indicating a gap, establishing need and problem, continuing a tradition, outlining purposes, and announcing the state of the present research. Specific linguistic features were used in each move and step although the students admitted that they had lack of knowledge with linguistic features. Based on the research finding, a Critical Genre-Based model for teaching problem statements in writing is proposed because this model has facilitative effect on consciousness-raising of the genres rhetorical structure.